Phase 1 evaluation of EZN‐2208, a polyethylene glycol conjugate of SN38, in children adolescents and young adults with relapsed or refractory solid tumors. Issue 10 (24th June 2014) - Norris, Robin E.; Shusterman, Suzanne; Gore, Lia; Muscal, Jodi A.; Macy, Margaret E.; Fox, Elizabeth; Berkowitz, Noah; Buchbinder, Aby; Bagatell, Rochelle
Abstract Background EZN‐2208 is a water‐soluble PEGylated conjugate of the topoisomerase inhibitor SN38, the active metabolite of irinotecan. Compared to irinotecan, EZN‐2208 has a prolonged half‐life permitting extended exposure to SN38. EZN‐2208 has demonstrated clinical tolerability and antitumor activity in adults with advanced solid tumors. This Phase 1 study evaluated the safety, pharmacokinetics, and preliminary antitumor activity of EZN‐2208 in children with relapsed or refractory solid tumors. Procedure EZN‐2208 was administered as a 1‐hour intravenous infusion once every 21 days at five dose levels (12–30 mg/m2). Filgrastim or pegfilgrastim was administered 24–48 hours after treatment with EZN‐2208. The rolling‐six design was used for dose determination. Results Thirty eligible patients (15 females; median [range] age 11.5 years [2–21 years]) were treated with EZN‐2208. Dose‐limiting diarrhea occurred in one patient receiving 16 mg/m2 and dose‐limiting dehydration was seen in one patient receiving 24 mg/m2. At dose levels above 16 mg/m2, Grade ≥3 myelosuppression was demonstrated in the majority of patients. Additional adverse events included nausea, vomiting, and fatigue. The maximum tolerated dose was identified as 24 mg/m2 due to dose‐limiting thrombocytopenia in two patients receiving 30 mg/m2. Two of nine patients with neuroblastoma who were evaluable for response had partial responses. Five patients (four with neuroblastoma) remained on study for ≥8 cycles. Conclusions EZN‐2208 was generally well‐tolerated and was associated with clinical benefit in patients with neuroblastoma. Pediatr Blood Cancer 2014; 61:1792–1797. © 2014 Wiley Periodicals, Inc.